1986
DOI: 10.1149/1.2108967
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Performance Improvement in Calcium‐Thionyl Chloride Cells

Abstract: Carbon cathode performance in ealcium-thionyl chloride cells was markedly improved with a cathode comprised of a mixture of high and low surface area carbon blacks. Addition of sulfur dioxide gas to the electrolyte further enhanced cathode performance and electrolyte conductivity. Load potentials and cathode life were nearly equal to that of the analogous lithium based system. The advantage of the calcium based system is its potential for greater safety.The calcium-thionyl chloride battery system has been attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Additional studies examined effects of SO2 gas additive, which further increased ionic conductivity. [39][40][41][42] For example, adding 10% (v/v) SO2 to 1.3 M Ca(AlCl4)2/SOCl2 led to an increase from ~6 to ~11 mS/cm at 25°C. [39] SO2 was also found to increase capacity, though this was proposed to be a physical rather than chemical effect resulting largely from physical release of SO2 at the cathode during discharge, increasing porosity and postponing cathode passivation.…”
Section: Early Understanding Of Ca Anodes and Ca 2+ Solvation In Primmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies examined effects of SO2 gas additive, which further increased ionic conductivity. [39][40][41][42] For example, adding 10% (v/v) SO2 to 1.3 M Ca(AlCl4)2/SOCl2 led to an increase from ~6 to ~11 mS/cm at 25°C. [39] SO2 was also found to increase capacity, though this was proposed to be a physical rather than chemical effect resulting largely from physical release of SO2 at the cathode during discharge, increasing porosity and postponing cathode passivation.…”
Section: Early Understanding Of Ca Anodes and Ca 2+ Solvation In Primmentioning
confidence: 99%
“…[39] SO2 was also found to increase capacity, though this was proposed to be a physical rather than chemical effect resulting largely from physical release of SO2 at the cathode during discharge, increasing porosity and postponing cathode passivation. [40,43] The reasons underlying improvements in ionic conductivity were not well understood until fundamental studies were conducted into Ca 2+ solvation in the analogous Ca-sulfuryl chloride (SO2Cl2) system. In 1982, Binder et al reported the Ca-SO2Cl2 primary battery as a potential improvement to Li-SO2Cl2.…”
Section: Early Understanding Of Ca Anodes and Ca 2+ Solvation In Primmentioning
confidence: 99%
“…Thus Eq. [6] holds for this calorimeter up to a temperature difference of about 3.6~ where the experimental K value is 0.6 W/~ At higher temperature differences air convection starts to be appreciable, and this leads to nonlinearity.…”
Section: Ss Donnectors~-~ Omentioning
confidence: 75%
“…1. This type of calorimeter is based on Newton's law dq/dt = W = K(T~ -T2) [6] where K is the thermal leakage factor of the calorimeter (i.e., of the thermal conductor around the internal cham- Equation [6] is valid only for temperature differences smaller than 2~176 (22). We found that choosing the heat conductor is not a simple task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation